2000
DOI: 10.1093/emboj/19.23.6612
|View full text |Cite
|
Sign up to set email alerts
|

Binding and cross-linking of tmRNA to ribosomal protein S1, on and off the Escherichia coli ribosome

Abstract: UV irradiation of an in vitro translation mixture induced cross-linking of 4-thioU-substituted tmRNA to Escherichia coli ribosomes by forming covalent complexes with ribosomal protein S1 and 16S rRNA. In the absence of S1, tmRNA was unable to bind and label ribosomal components. Mobility assays on native gels demonstrated that protein S1 bound to tmRNA with an apparent binding constant of 1 3 10 8 M ±1 . A mutant tmRNA, lacking the tag coding region and pseudoknots pk2, pk3 and pk4, did not compete with full-l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
139
0
2

Year Published

2001
2001
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 110 publications
(144 citation statements)
references
References 59 publications
3
139
0
2
Order By: Relevance
“…Wower et al (10) detected direct and specific S1⅐SsrA binding and used crosslinking studies to define sites of contact between S1 and individual bases in pseudoknots PK2, PK3, and the PK3-PK4 junction, as well as a contact in the tag-coding region of SsrA. The majority of the nucleotides crosslinked to S1 were within PK3, in agreement with our finding that PK3 is an important determinant of S1 binding.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Wower et al (10) detected direct and specific S1⅐SsrA binding and used crosslinking studies to define sites of contact between S1 and individual bases in pseudoknots PK2, PK3, and the PK3-PK4 junction, as well as a contact in the tag-coding region of SsrA. The majority of the nucleotides crosslinked to S1 were within PK3, in agreement with our finding that PK3 is an important determinant of S1 binding.…”
Section: Discussionsupporting
confidence: 89%
“…The majority of the nucleotides crosslinked to S1 were within PK3, in agreement with our finding that PK3 is an important determinant of S1 binding. When S1 was depleted from in vitro-translation extracts, SsrA RNA did not associate with ribosomes (10). S1 is conserved in most bacteria and has been implicated in the selection of translation-start sites, especially for mRNAs lacking Shine-Dalgarno ribosome binding sites upstream of the ATG initiation codon (16,18).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Elongation factor Tu is important for initial tmRNA binding to the ribosome (9) and may also facilitate the structural rearrangement of the tmRNA molecule (10). Ribosomal protein S1 may bind to the mRNA part of tmRNA (11) in a manner similar to that of cellular mRNA (12). Small protein B (SmpB) is the only key protein known to be essential and specific for trans-translation.…”
mentioning
confidence: 99%
“…The extensive structural variation in diverse tmRNA sequences, and the sporadic occurrence of some helical regions, has been noted previously (Williams & Bartel 1998;Zwieb et al+, 1999)+ Extensive structural variability occurs even within the gamma-group proteobacterial sequences reported here, confirming the notion that much of the tmRNA structure can vary with little effect on its basic function+ Indeed, experimental modifications of the E. coli tmRNA have shown that three of the pseudoknots (pk2, pk3, and pk4; Fig+ 4) are completely interchangeable and can even be replaced by unstructured regions with no significant loss of function (Nameki et al+, 2000)+ We suspect that these phylogenetically volatile regions of the structure occur on the surface of the functional unit because of spacefilling constraints (Burgin et al+, 1990), whereas conserved structural elements and sequences are expected to form the functional core of tmRNA+ A recent crosslinking study also may shed some light on the variability of tmRNA across different lineages+ In this study, the investigators discovered substantial crosslinking between tmRNA and ribosomal protein S1 (Wower et al+, 2000)+ Ribosomal protein S1, however, is not found in all bacterial lineages, specifically the Low GϩC group of Gram-positive bacteria+ Thus, at least in this group of Bacteria, tmRNA must find an alternative binding site+ If the binding site of tmRNA can change radically, as this study suggests, then such extensive variability in tmRNA secondary structure may be expected+…”
Section: Discussionmentioning
confidence: 80%